Advocacy campaign on youth investment - Ricafort, Godofredo S. Jr. (2013)
Investment is known for its economic term, by playing a risk (money/business) on a certain process, hoping for an increase in return. But if we look at the work n a deeper perspective (based on other dictionary definition) Investment is also, said to be "an act of committing and devoting (time, ability, patience, etc.) for a purpose of attaining or achieving something. Applying it in the country, we just can't depend on a term or on a form of investment which will bring the people on a dependency setting or on a sort of a barrier/limitation on doing something. We should consider our people, whatsoever status they're in, "as investors", especially the young ones (considering the hope of the country : Jose Rizal) to be the main definition and image of investment. Youth can invest in small things that could come-up with endless opportunity, that would apply/continue learning, stand for leadership and skills that would somehow, come up on a long term development, progress and success.
"April 2013"
Thesis (BFA)--University of the Philippines Diliman.
Keywords: Youth; Investment; Advocacy campaign